Paragenesis Mineral Serpentin Pada Batuan Ultramafik Daerah Tampanombo, Kabupaten Tojo Una-Una, Provinsi Sulawesi Tengah - Muslimin U Botjing; Djamal Adi Nugroho Uno; Michael Sandi; Andi Arham Adam; Sriyati Ramadhani (Universitas Negeri Gorontalo, 2026)
The Tampanombo area, Tojo Una-Una Regency, Central Sulawesi Province, is composed of ultramafic rocks that have undergone intensive serpentinization due to interactions between primary silicate minerals and hydrothermal fluids. This study aims to examine the paragenesis of serpentine minerals in ultramafic rocks using petrographic, geochemical, and electron microscopy approaches. The methods employed include thin-section petrographic analysis, XRF, and SEM-EDS. Petrographic observations reveal characteristic serpentinization textures, including mesh texture as the initial product of olivine hydration, bastite texture formed by pyroxene replacement, and hourglass texture indicating serpentine recrystallization. Interlocking and interpenetrating textures in antigorite were also observed, indicating mutually penetrating crystal growth associated with increasing temperature and pressure during advanced metamorphic stages. The presence of type-1, type-2, and type-3 veins suggests multiple phases of fluid circulation during rock evolution. XRF analysis indicates high MgO content along with variations in SiO₂, Fe₂O₃, and LOI, reflecting different degrees of serpentinization among samples. SEM-EDS data confirm the dominance of Mg, Si, and O as the main constituent elements of serpentine minerals, as well as the presence of Fe associated with magnetite formation. Based on textural and geochemical data, the paragenesis of serpentine minerals in the study area includes three main subprocesses: hydration, serpentine recrystallization, and deserpentinization (dehydration) related to prograde metamorphism.